CARROTS JUICE FOR DYSMENORRHEA - Hastuti, Puji; Aini, Fajaria Nur; Sumiyati, Sumiyati (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The incidence of dysmenorrhea (menstruation pain) was reported at a moderate level (64.25%), ranged from 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. Most Indonesian women used herbs to reduce the pain, yet, only few who understood that carrots can be used. Carrots contains a lot of beta carotene, flavonoids and saponins that works as analgesic and anti- inflammatory effect. It inhibits the enzyme phospholipase and lipooksigenase enzymes that would inhibit prostaglandin release. Aims: The objective of this research is to analyze the effect of carrots juice to reduce dysmenorrhea in midwifery student. Method: this research employed pre-experimental design, with pretest-posttest one group design. The carrot-free varieties of water was set as independent variable, whilst different levels of dysmenorrhea pain as dependent variable. Twenty five female students was selected randomly as sample from 172 studentsâ population. Prior to treatment, respondents were asked to fill out a questionnaire about the degree of pain experienced, then given carrot juice made from 250 grams of carrots, 100 cc of water and 2 tablespoons of sugar and drink 2 times (morning and evening). After administering carrot juice, respondents again filled out questionnaires about the level of dysmenorrhea pain. Results: Prior to the intervention, 72% participant experienced mild pain whilst 20% suffered from moderate pain and 8% felt severe pain. After the provision of carrots juice, the vast majority experienced no pain (68%), 24% mild and 8% felt moderate pain. No participants reported suffered from severe pain. The results of Wilcoxon Match Paired Test analysis shows that there is influence of giving of carrots juice to various level of dysmenorrhea in student with p = 0.001. Conclusion: There is an effect of giving carrots water to various levels of dysmenorrheal pain in the students. So it is advisable for teenagers or adults to increase knowledge related to dysmenorrhea and to provide carrot juice as an alternative to overcome dysmenorrhea pain.Â